Analysis of Two Methods for Inventorying the Tree Component in a Section of the SiempreVerde trail in Santa Rosa National Park - Jiménez, José (2010)
We found 16 families, 23 species and 54 individuals of trees in the Siempre Verde trail. Anacardiaceae, with 3 species, was the tree family with more diversity. Moraceae, with 13 specimens of Castilla elástica was the family with the highest abundance. Furthermore, we compared two methods to assess the spatial locations of more than (>) 10 cm of diameter trees, and we concluded that the measuring tape and compass method was the most precise within a natural covered area.